Ductility of Precast Concrete Column Beams Using Dowels - Herman Tumengkol; Carter Kandou; Don Kabo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Precast concrete structures are considered as monolithic structures, flexural reinforcement and beam column joint shear can be planned based on design capacity. This research is an experimental study. The objective is to assess the ductility of precast concrete column beams utilizing dowels. The test specimens comprise three configurations: monolithic beam column (BN), 2 post precast beam column (BG 1), and 4 post precast beam column (BG 2), with respective displacement values of 37.4 mm, 42.7 mm, and 47 mm. This research was carried out in the stages of calculating displacement ductility using displacement parameters, and curvature ductility using parameters of cross-sectional curvature or curvature values and load values due to cyclic loads. The research results show that the displacement ductility values for test specimens BN, BG 1 and BG 2 are 2.34, 2.21 and 2.06 respectively. The curvature ductility value for test specimens BN, BG 1 and BG 2 is more than the value required in ASCE 41-17, namely 0.01 in the LS condition and in the CP condition it is 0.015. Additionally, these values surpass the stipulated requirements. This leads to the conclusion that beam column connections, whether monolithic or precast, exhibit exceptional performance in withstanding earthquake loads under both moderate seismic conditions (moderate earthquakes) and severe seismic conditions (strong earthquakes)